THE RESULTS OF A STUDY OF THE POPULATION AND DISTRIBUTION OF SNOW LEOPARDS (UNCIA UNCIA SCHREBER 1775) OF TSAGAAN SHUVUUT NATURAL RESERVE THROUGH AUTOMATIC CAMERAS AND FUR SPOTS - Tugsuu, B; Ganbat, G; Munkhtsog, B (Mongolian Journal of Agricultural Sciences, 2015)
Snow leopard is one of the endangered species that has been listed in the Red book of Threatened Species of the International Union for Conservation of Nature (IUCN) as well as in 11 countries of Central Asia, including Mongolia. The main reasons of endangerment include the disappearance and decrease of their prey population due to livestock feeding into their habitat, illegal hunting to sell beautiful skins, hunting of their prey and vanishing of their habitat due to the impacts of human activities. Determining the habitation, population number, and density and comprehensively identifying the factors of influence have vital importance in conserving the population of snow leopards in Mongolia and Russia, the northernmost habitants of the world’s snow leopards. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 131-135